2021
DOI: 10.14718/revfinanzpolitecon.v13.n1.2021.4
|View full text |Cite
|
Sign up to set email alerts
|

The Asymmetric Relationship Between Military Expenditure, Economic Growth and Industrial Productivity: An Empirical Analysis of India, China and Pakistan Via the NARDL Approach

Abstract: This research work aims to verify how military expenditure promotes economic growth and industrial productivity, as suggested by the Military Keynesianism postulate. The NARDL method is employed to achieve the above objective on the panel data of India, China, and Pakistan, covering the period between 1990 and 2018. The study finds that the positive and negative impact of military expenditure has a significant positive and negative effect on economic growth in the long run for China and India; however, in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…On the other hand, the "Benoit Hypothesis," which suggests that military expenditures positively affect economic growth, was confirmed for the panel. Our panel results are consistent with the findings of Macnair et al (1995), Asseery (1996), Brumm, 1997, Sezgin (1997, Murdoch et al (1997), Lai et al (2002), Yıldırım et al (2005, Malizard (2010), Alptekin andLevine (2012), Ismail (2017), Dimitraki and Win (2021) and Aijaz Syed (2021).…”
Section: Conclusion and Policy Recommendationssupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, the "Benoit Hypothesis," which suggests that military expenditures positively affect economic growth, was confirmed for the panel. Our panel results are consistent with the findings of Macnair et al (1995), Asseery (1996), Brumm, 1997, Sezgin (1997, Murdoch et al (1997), Lai et al (2002), Yıldırım et al (2005, Malizard (2010), Alptekin andLevine (2012), Ismail (2017), Dimitraki and Win (2021) and Aijaz Syed (2021).…”
Section: Conclusion and Policy Recommendationssupporting
confidence: 92%
“…There are no definite results in the studies that followed. While some studies (Macnair et al, 1995;Asseery, 1996;Brumm, 1997;Sezgin, 1997;Murdoch et al, 1997;Lai et al, 2002;Yildirim et al, 2005;Malizard, 2010;Alptekin and Levine, 2012;Canbay and Mercan, 2017;Ismail, 2017;Dimitraki and Win, 2021;Aijaz Syed, 2021) are for the Benoit hypothesis, the others (Faini et al, 1984;Deger, 1986;Dunne and Vougas, 1999;Dunne et al, 2002;Klein, 2004;Yang et al, 2011;D'Agostino et al, 2019;Dunne and Tian, 2015;Luqman and Antonakakis, 2021) are against the hypothesis. Besides, some other studies (Biswas and Ram, 1986;Alexander, 1990;Dakurah et al, 2001;Aye et al, 2014;Gokmenoglu et al, 2015;Manamperi, 2016) did not find sufficient evidence regarding the relationship between economic growth and military expenditures.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The insignificance of terrorism and military spending is explained by the failed efforts of the government at combating terrorism despite increasing defence spending, holding rehabilitation programs for prisoners and intensively campaigning against terrorism. Syed (2020) used the nonlinear variant of the ARDL framework (NARDL), to investigate the growth effects of military spending in Pakistan, China and India during the 1990–2018 period. The result showed that military spending is growth-enhancing and has short-run symmetric and long-run asymmetric impacts on the Chinese and Indian economies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using quantile ARDL model, Luqman and Antonakakis (2021) revealed that military spending has a negative influence on economic growth and human development in Palistan. However, for the panel of Pakistan, India, and China according to (Syed, A. A.…”
Section: Literature Reviewmentioning
confidence: 99%